The Effect of Different Agroecological Zones on Body Weight Change, Litter Size, and Profitability of Bligon Goats in Bantul Regency, Special Region of Yogyakarta - Lusia Komala Widiastuti; Sigit Bintara; I Gede Suparta Budisatria; Bayu Andri Atmoko (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
This study aims to identify the differences in agroecological zones on changes in body weight, litter size, and profitability of Bligon goats in Bantul District, Special Region of Yogyakarta. This study involved 56 farmers consisting of 11 farmers in coastal areas (zone IV), 21 farmers in the lowlands (zone IV), and 24 farmers in hilly areas (zones I, II, and III). This study also used 120 does of Bligon goats consisting of 40 goats from each area. The farmers and Bligon goats were selected by purposive sampling technique in different agroecological zones classified based on the slope of the land. The design used was Completely Randomized Design (CRD) with the agroecological zones as a treatment factor. This study used a survey method. Data were analyzed descriptively and quantitatively using one-way ANOVA at the 5% level. The results showed that the body weight of Bligon goats from the beginning of kidding to three months or at the weaning period did not have a significant difference, and the litter size was also not significantly different. Profitability analysis using Revenue Cost Ratio (R/C Ratio) and Return on Investment (ROI) showed that farmers in coastal agroecological zones have higher profitability than those in lowland and hilly agroecological zones with a net cash flow of IDR 1,219,000, 00, R/C Ratio of 1.43, and ROI of 44.26. Based on this analysis, it can be concluded that changes in body weight and litter size of Bligon goats in different agroecological zones are the same. Based on the profitability analysis, all farmers in different agroecological zones benefit from raising Bligon goats, but the highest profitability is found in farmers in the coastal agroecological zone